Aluminium blunts the proliferative response and increases apoptosis of cultured human cells: putative relationship to alzheimer's disease - Prolo, Paolo (Biomedical Informatics Publishing Group, 2007)
Aluminium (Al) has been investigated as a neurotoxic substance. Al ranks among the potential environmental risk factors for Alzheimer's disease (AD). Epidemiological studies tested the relationship between Al in drinking water and AD, showing a significant correlation between elevated levels of monomeric Al in water and AD, although data to date remain inconclusive with respect to total Al. The aim of this study was to test whether or not Al exacerbates cellular toxicity mediated by the amyloid β (Aβ) peptide. We evaluated the role of Al in modulating programmed cell death (apoptosis) in human cell cultures. We used the osteosarcoma cell line monolayer (SaOs-2) to demonstrate that treatment of SaOs-2 cultures with the Aβ peptide mid-fragment (25 to 35) at nano M, followed by co-incubation with physiological concentrations of aluminium chloride, which release monomeric Al in solution, led to marked expression of caspase 3, but not caspase 9, key markers of the apoptotic process. The same experimental conditions were shown to blunt significantly the proliferative response of normal human peripheral blood mononuclear cells (PBMC) to phytohemagglutinin (PHA) stimulation. Our observations support the hypothesis that Al significantly impairs certain cellular immune responses, and confirm that Al-mediated cell toxicity may play an important role in AD.